Digital Information Access, Peer Social Effect, and Combine Harvester Service Adoption: Evidence from Rice Farmers in East Java, Indonesia - Mustaqim, Muhammad Izak; Syafrial; Toiba, Hery; Minh-Tu, Le (Department of Social Economy, Faculty of Bio-Industry, Agriculture and Forestry, University of Brawijaya, 2026)
Purpose: This study examines how peer social effect (PSE) is associated with smallholder rice farmers' decisions to adopt combine harvester (CH) services in East Java, Indonesia, and tests whether this association is moderated by digital information access, household operational assets, and farmer-group membership — challenging the conventional assumption in diffusion literature that peer exposure uniformly accelerates technology uptake. Design/Methodology/Approach: Cross-sectional survey data from 300 rice farmers are analyzed using an IV-Probit model. Endogenous PSE is instrumented with average PSE per referral and a social diversity index; interaction terms capture the moderating role of digital access, car ownership, and farmer-group membership. Identification and weak-instrument diagnostics support the validity of the IV strategy. Findings: Contrary to conventional diffusion expectations, PSE shows a negative and statistically significant association with CH adoption, suggesting that local peer environments transmit caution and norm-conforming restraint rather than pro-adoption signals. Digital information access is positively associated with adoption and significantly attenuates this negative PSE-adoption association, indicating that online information helps farmers verify and act on peer-derived knowledge. Interaction effects for car ownership and farmer-group membership are positive but statistically non-significant, though farmer-group membership retains a significant direct association with adoption. Distance to CH providers and limited public Wi-Fi proximity jointly constrain adoption, reinforcing digital access as an adoption channel, while participation in Tebas (pre-harvest crop-purchase) arrangements further limits adoption incentives. Originality/Value/Novelty: The study departs from the standard diffusion assumption that peer effects uniformly accelerate technology adoption, showing instead that peer influence can restrain uptake through norm-conforming caution. By identifying digital verification as the mechanism through which this restraint is attenuated, the study links social and digital infrastructure in agricultural mechanization research — a connection largely unaddressed in prior peer-effect and technology-adoption literature — and offers a socially restrain framework for understanding mechanization service-use decisions.